Cytotoxicity induced by Aeromonas schubertii is orchestrated by a unique set of type III secretion system effectors - Michova, Hana; Pliva, Jan; Jirsova, Anezka; Jurnecka, David; Kamanova, Jana (Veterinary research, 2025)
The type III secretion system (T3SS) is an important virulence factor of Gram-negative bacteria, including the genus Aeromonas, which represents a diverse group of aquatic bacteria. One member of the genus, Aeromonas schubertii, is an emerging pathogen in aquaculture, causing high mortality in snakehead fish. Infections are associated with the formation of white nodules in the internal organs, likely resulting from A. schubertii-induced apoptosis and/or necrosis. The present study investigates the type strain A. schubertii ATCC 43700, which encodes two distinct T3SSs located within Aeromonas pathogenicity islands 1 and 2, referred here to as API1 and API2. We analyzed their role in A. schubertii-induced cytotoxicity and identified novel T3SS effector proteins. Infections of HeLa cells revealed that API1, but not API2, mediates cytotoxicity and induces both apoptotic and necrotic cell death. Moreover, proteomic analysis identified seven candidate effectors secreted by the API1 injectisome. These included two previously described effectors, AopH and AopO from A. salmonicida, as well as five novel effectors named AopI, AopJ, AopL, AopT, and AopU, whose injection into host cells was validated using a split luciferase reporter system. Functional characterization showed that AopL, a homolog of Vibrio parahaemolyticus VopQ, induces caspase-3/-7-independent necrosis, while AopI, a homolog of ExoY from Pseudomonas aeruginosa, suppresses caspase-3/-7 activation and necrosis, revealing a pro-survival function. These results demonstrate the critical role of the API1 injectisome in A. schubertii-induced cytotoxicity and provide experimental identification of novel Aeromonas effectors that cooperate to fine-tune host cell cytotoxicity.
Keywords: VopQ; Virulence Factors; apoptóza; type III secretion system effectors; HeLa Cells; Type III Secretion Systems; sekreční systém typu III; cytotoxicity; gramnegativní bakteriální infekce; Aeromonas schubertii; ExoY; Bacterial Proteins; zvířata; Humans; Aeromonas; nemoci ryb; Gram-Negative Bacterial Infections; Fish Diseases; faktory virulence; bakteriální proteiny; HeLa buňky; lidé; Apoptosis; Animals